Evaluation of phosphine genotoxicity at occupational levels of exposure in New South Wales, Australia. Issue 10 (October 1994) - Barbosa, A; Bonin, A M
Abstract : Phosphine has been claimed to cause chromosomal damage at exposures close to the current time weighted average exposure standard of 0.3 ppm (0.4 mg/m3). The current study involved 31 phosphine fumigators and 21 controls during the high fumigation season. All were volunteers and were evaluated for genotoxicity variables, including micronuclei in peripheral blood lymphocytes and urine mutagenicity. In parallel, all fumigators and 17 controls were evaluated for full haematology, multiple biochemical analysis, whole blood organochlorines, and whole blood and serum cholinesterase activity. The results for micronuclei showed no significant differences between fumigators and controls, but detected a strong association between age and increased frequency of micronuclei. Measurement of urine mutagenicity did not show any significant difference between fumigators and controls, but did show increased excretion of mutagens in smokers. All haematological and biochemical variables were within normal ranges, except for some non-specific changes in biochemistry. At monitored occupational exposures of < 2.4 ppm/h our results show no association between phosphine exposure and genotoxic or toxicological effects in fumigators.